Pengaruh Penggunaan Pupuk Anorganik dan Pupuk Semai Mikrobia terhadap Pertumbuhan dan Produksi Kapas (Gossypium hirsutum L.) - Guntoro, Dwi; Chozin, M. A.; Dwirestina, Dini (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
effect of inorganic fertilizer dosage and concentration of Semai Mikrobia fertilizer on cotton growth and production was studied at Cikabayan greenhouse, IPR. The experiment was arranged in split plot design with three replicates. The dosages of inorganic fertilizers as the main plot and the concentration of Semai Mikrobia as sub plot. The dosages of inorganic fertilizers were no fertilizer, 50% recommended dosage, and IOO% recommended dosage and the concentrations of Semai Mikrobia were 0 cc/l water, 4 cc/l water, 8 cc/l water, and I2 cc/l water. The results indicated that the application of Semai Mikrobia fertilizer up to I2 cc/l did not affect growth and production of cotton. There was no interaction effect between the dosage of inorganic fertilizer and Semai Mikrobia concentration. Inorganic fertilizer application at IOO% recommended dosage increased height and the number of generative branch compared with no fertilizer.